Cognitive Radio Receiver Front-Ends RF/Analog Circuit Techniques - Sadhu, Bodhisatwa (Analog Circuits and Signal Processing,, 2014)
This book focuses on the architecture and circuit design for cognitive radio receiver front-ends.Â  The authors first provide a holistic explanation of RF circuits for cognitive radio systems. This is followed by an in-depth exploration of existing techniques that can be utilized by circuit designers. Coverage also includes novel circuit techniques and architectures that can be invaluable for designers for cognitive radio systems.Â Â  â_¢Â Discusses in detail the circuit-level challenges that exist for cognitive radio systems; â_¢Â Provides readers with a holistic understanding of RF circuits for cognitive radio systems; â_¢Â Enables communications engineers and systems designers to design better cognitive radio architectures and communication protocols.